Two Lactobacillus Species Inhibit the Growth and α-Toxin Production of Clostridium perfringens and Induced Proinflammatory Factors in Chicken Intestinal Epithelial Cells in Vitro - Guo, Shuangshuang; Liu, Dan; Zhang, Beibei; Li, Zhui; Li, Yehan; Ding, Binying; Guo, Yuming (Frontiers in Microbiology, 2017)
Clostridium perfringens is the causative pathogen of avian necrotic enteritis. Lactobacillus spp. are well-characterized probiotics with anti-microbial and immune-modulatory activities. In the present study, we investigated the effects of L. acidophilus and L. fermentum on the growth, α-toxin production and inflammatory responses of C. perfringens. In in vitro culture experiments, both lactobacilli inhibited the growth of C. perfringens (P < 0.01), accompanied with a decrease in pH (P < 0.01). Supernatants from lactobacilli cultures also suppressed the growth of C. perfringens during 24 hours of incubation (P < 0.01), but this inhibitory effect disappeared after 48 hours. Both lactobacilli decreased the α-toxin production of C. perfringens (P < 0.01) without influencing its biomass, and even degraded the established α-toxin (P < 0.01). Lower environmental pH reduced the α-toxin production as well (P < 0.01). Preincubation with L. acidophilus decreased the attachment of C. perfringens to cells (P < 0.01) with the cell cytotoxicity being unaffected. Both lactobacilli pretreatment reduced the up-regulation of proinflammatory factors, peptidoglycan receptors and nuclear factor kappa B p65 in C. perfringens-challenged chicken intestinal epithelial cells (P < 0.05). In conclusion, L. acidophilus and L. fermentum inhibited the pathological effects of C. perfringens in vitro conditions.